2022
DOI: 10.2196/36052
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based, Provider-Driven Mobile App to Enhance Patient Care Coordination Between Dialysis Facilities and Hospitals: Development and Pilot Implementation Study

Abstract: Background We piloted a web-based, provider-driven mobile app (DialysisConnect) to fill the communication and care coordination gap between hospitals and dialysis facilities. Objective This study aimed to describe the development and pilot implementation of DialysisConnect. Methods DialysisConnect was developed iteratively with focus group and user testing feedback and was made available to 120 potential use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Fidelity to the intervention was suboptimal; although most hospital admissions were captured in the system, the number of users engaged with DialysisConnect was low, even among some of the most critical roles for care transitions (eg, dialysis nurses and social workers). 19 Most, but not all, inpatient care for Emory Dialysis patients occurs at EUHM; we were not able to track inpatient admissions or other hospital utilization outside of EUHM, and this potential loss to follow-up may have been greater among other dialysis patients admitted to EUHM. Although, loss to follow-up because of mortality could lead to selection bias, sensitivity analyses showed that results were not substantially changed with the exclusion of discharges followed by mortality within 30 days.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Fidelity to the intervention was suboptimal; although most hospital admissions were captured in the system, the number of users engaged with DialysisConnect was low, even among some of the most critical roles for care transitions (eg, dialysis nurses and social workers). 19 Most, but not all, inpatient care for Emory Dialysis patients occurs at EUHM; we were not able to track inpatient admissions or other hospital utilization outside of EUHM, and this potential loss to follow-up may have been greater among other dialysis patients admitted to EUHM. Although, loss to follow-up because of mortality could lead to selection bias, sensitivity analyses showed that results were not substantially changed with the exclusion of discharges followed by mortality within 30 days.…”
Section: Discussionmentioning
confidence: 97%
“…18 To address this gap, we introduced "DialysisConnect," a secure, web-based, 2-way communications platform that allowed direct communication between providers, automated messages at admission and discharge, and timely exchange of critical discharge information (Fig S1). 19 The system was available to physicians, advanced practice providers, nurses, social workers, and other individuals as identified by the site champions. 19 We piloted Dialy-sisConnect at Emory University Hospital Midtown (EUHM) and 4 affiliated Emory Dialysis facilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation